Metformin Is the First Choice of Oral Medicated Breastfeeding Mothers - Devajit Mohajan; Haradhan Kumar Mohajan (Innovation in Science and Technology, 2024)
Diabetes mellitus (DM) is a group of metabolic disorders in which there are high levels of glucose in the blood. The effects of DM are long-term damage, dysfunction and failure of various organs. Metformin is a common first-line treatment for type 2 diabetes (T2D) patients. It is one of the oldest treatments for diabetes, dating back to the 1960s. Some scholars in their studies have found that Metformin used by mothers is safe for their breastfeed infants. Most T2D breastfeeding mothers choice Metformin for their initial treatment of diabetes. Sometimes Metformin is found in low levels in the serum of breastfed infants. But no adverse effects are seen when breastfeeding women use Metformin as an oral medication. Although metformin does not lower plasma glucose, it should be used by breastfeeding mothers very carefully and should stop immediately if any side effect is observable.